Prediction model for utilization of complementary and alternative medicine for sports injuries among Korean elite collegiate athletes - Ye-Seul Lee; Deuk Su Park; Jae Keun Oh; Song-Yi Kim (Integrative Medicine Research)
Background: The purpose of this study was to describe the use of complementary and alternative medicine (CAM) services by Korean elite collegiate athletes and to examine the factors influencing the utilization of CAM, or Korean Medicine (KM). Methods: Students in Korea National Sport University (KNSU) enrolled and in training during August to December 2017 completed the survey. Data from the survey was analyzed through path analysis. Results: Students who were training in the Department of Physical Education, KNSU (n = 624, 70% males, mean age 21.3 ± 1.2) participated in this study. 15% of the respondents chose KM clinics for sports injuries, a higher rate than that of the general population, and 44% of KM interventions involved acupuncture. In the path analysis, sports injuries were positive predictors for utilization of medical services and the perception of KM, and KM utilization and the perception of KM were positive predictors of the willingness to receive KM treatments. Conclusions: The use of KM such as acupuncture was relatively high in elite collegiate athletes. The perception of KM and willingness to receive KM treatments were mediated by previous KM experiences. A higher accessibility towards KM treatments are necessary.